First record of Cyprideis torosa (Jones, 1850) (Crustacea: Ostracoda) in the East of Al-Hammar Marshes, Southern Iraq - Khalifa, Mohammed G.; Ajeel, Shaker G. (Mesopotamian Journal of Marine Sciences, 2022)
CyprideCyprideis torosa is recorded for the first time in east Al-Hammar marshes and it was collected from three stations (Al-Sallal, Al-Nagara and Al-Masʼhab) in east of Al-Hammar marshes between January and December 2021. The ecological parameters measured were water temperature, dissolved oxygen, pH, conductivity, salinity and turbidity and were related to the presence or absence of the species in question. is torosa is recorded for the first time in east Al-Hammar marshes and it was collected from three stations (Al-Sallal, Al-Nagara and Al-Masʼhab) in east of Al-Hammar marshes between January and December 2021. The ecological parameters measured were water temperature, dissolved oxygen, pH, conductivity, salinity and turbidity and were related to the presence or absence of the species in question.